THE SYNTACTICAL ANALYSIS OF THE INFLUENCE OF SPEECH THERAPY TO POST STROKE PATIENTS WITH BROCA’S APHASIA’S SPEECH ABILITY - Hilfa Yulia; Hermawati Syarif; Leni Marlina (Universitas Negeri Padang, 2018)
Although there are many studies about post-stroke, the research about this study is rare. This study aims to analyze the influence of the speech ability of post-stroke patients affected by Broca aphasia before and after speech therapy in terms of syntax. This study uses a qualitative description method. The data in this study were conversations from three post-stroke patients before and after speaking therapy on YouTube videos. This data were analyzed based on Language Acquisition theory regarding language acquisition classifications. There are several types of syntactic structures in language acquisition of the patients before and after speaking therapy and their influence on their speech ability of post-stroke patients in this thesis, Patients no longer experience holophrastic (one word) and two words. This study shows the ability to utter of three post-stroke patients before speaking therapy of the type of syntactic structure, namely, telegraphic speech (70.27%), short sentence is (16.21%) and two words is (8.10%) and holophrastic (5.40%) . The ability to utter of three post-stroke patients after speech therapy of the type of syntactic structure of telegraphic speech is (66.32%), short sentence is (33.67%), holophrastic and two words are (0%). It can be concluded that speech ability of patients is limited to simple sentences after speech therapy.